Improving Vascular Access Dressing Integrity in the Acute Care Setting: A Quality Improvement Project. Issue 5 (29th September 2021) - DeVries, Michelle; Sarbenoff, Jill; Scott, Nancy; Wickert, Margaret; Hayes, Lisa Marie
Abstract : PURPOSE: The purpose of this quality improvement project was to evaluate transparent vascular access dressings and the use of a liquid gum mastic adhesive on improving dressing integrity over peripheral intravenous (PIV) insertion sites without increasing medical adhesive-related skin injuries (MARSIs) such as tears. PARTICIPANTS AND SETTING: A multidisciplinary team consisting of specialists in infection prevention, vascular access, nursing professional development, materials management, and WOC nurses met to review current audit data and available products to trial on 2 intermediate care units in our 2 hospitals in Indiana with a combined average daily unit census of 35 patients. APPROACH: Four dressing protocols—including our existing dressing with education, and an updated dressing with education, and the updated and new dressing, both with education and the addition of a gum mastic adhesive agent—were sequentially implemented by nurses on the units, each over a 2-week period. The goal was for 80% of the dressings to remain with all 4 corners fully intact without reinforcement at day 7, or sooner if PIV was discontinued before day 7. Data were reported as frequencies for intact dressings and skin complications. OUTCOMES: Education combined with the original dressing and the updated dressing did not achieve the goal of 80% fully intact dressings in the samples evaluated. The addition of the adhesive agent to the updated and new dressings with education exceeded the 80% goal. In addition, there were zero exposed PIV insertion sites and no documented MARSI in any of the 4 protocols. IMPLICATIONS FOR PRACTICE: We continued to collect postproject data of 30, 049 vascular access sites including central line catheters and observed the same effectiveness of incorporating a gum mastic adhesive on dressing integrity. This practice change has now become standard of care in our institution.